Preface - Ramos, M. J. (2022)
The context of the research journey that has led to the present book is a body of work of mainly 16thand 17thcentury textual documents concerning a mission of the Society of Jesus that began in Ethiopia in 1555 and ended in 1633, when their last members were expelled from the country. Throughout its duration and afterwards, up to the 18thcentury, the mission was the subject of an extended set of scriptural, archival and literary documents, produced by the Jesuits themselves and others. Sources include contemporary Iberianroyal and governmental authorities in India, writings in Ge’ez (Ethiopia’s classical liturgical language) and works of local scholars, royal chronicles and hagiographical sources, etc. Most of these documents are well known today and regularly feed a rich field of research on that period of Ethiopian history. However, despite the fact that the presence of the mission in Ethiopia has been carefully studied, there has still been little research on the mission’s own production of written material, based on those sources and their history.